A supportive organisational culture for project management in matrix organisations: A theoretical perspective - J. M. Morrison; C. J. Brown; E. V.D.M. Smit (South African Journal of Business Management, 2006)
Although the need for organisational cultures to be supportive of project management is frequently expressed in the project management literature, a comprehensive explanation of what supportiveness comprises, has not yet come to light. The field of organisational culture research recognises culture as a complex and multi-dimensional topic. To date, the project management literature has taken a superficial view of culture instead. It specifically lacks progress towards a converging set of organisational culture dimensions as predictors of effective project management. Against this apparent shortcoming, a research project was launched, aiming to define the dimensions of a project management supportive organisational culture. This article presents the findings of the literature study phase of this research. Ample evidence was found, although dispersed amongst a diversity of project management research themes, to give substance to the notion and to postulate a multi-dimensional framework of organisational culture expected to be relevant to project management. The researchers make no premature claims about the conclusiveness of the proposed framework, but introduce it as a thoroughly researched hypothesis for empirical study. The study makes its contribution by converging literature evidence, previously lacking such coherence, into a consolidated organisational culture perspective. The hope is that it will spark further theory development in respect of the organisational context of project management.
Keywords: 650